2011
DOI: 10.1099/mic.0.048454-0
|View full text |Cite
|
Sign up to set email alerts
|

Acyl depsipeptide (ADEP) resistance in Streptomyces

Abstract: ADEP, a molecule of the acyl depsipeptide family, has an antibiotic activity with a unique mode of action. ADEP binding to the ubiquitous protease ClpP alters the structure of the enzyme. Access of protein to the ClpP proteolytic chamber is therefore facilitated and its cohort regulatory ATPases (ClpA, ClpC, ClpX) are not required. The consequent uncontrolled protein degradation in the cell appears to kill the ADEP-treated bacteria. ADEP is produced by Streptomyces hawaiiensis. Most sequenced genomes of Strept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 39 publications
0
54
0
Order By: Relevance
“…Surfactin belongs to the lipodepsipeptide class of natural products, which includes antibiotics such as daptomycin and ADEPs (46,47). Although the surfactin hydrolase had activity against the lipopeptide plipastatin in addition to surfactin, other compounds tested were not substrates for the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Surfactin belongs to the lipodepsipeptide class of natural products, which includes antibiotics such as daptomycin and ADEPs (46,47). Although the surfactin hydrolase had activity against the lipopeptide plipastatin in addition to surfactin, other compounds tested were not substrates for the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing of resistant mutants revealed that the potential target was Clp protease, but as Clp protease is not required for normal growth in these organisms it was surprising that ADEPs exhibited their bactericidal effect through an interaction with a dispensable protease 90 . An in vitro peptidase assay using ClpP protease from Bacillus subtilis revealed that ADEPs activated proteolysis.…”
Section: Clp Proteasementioning
confidence: 99%
“…The natural product cyclomarin is difficult to synthesize or modify, and exhibited high clearance (due to hepatic clearance) and a short half-life when tested in mice (V. Dartois, personal communication). Although ADEPs are attractive as they are able to kill organisms even though their target is often not essential for survival, loss of ClpP activity renders these compounds inactive, resulting in high rates of resistance in vitro 90 . However, as there is strong selection to retain protease activity during infection, loss of ClpP activity as a resistance mechanism seems to be unlikely to occur during treatment, but this has yet to be confirmed.…”
Section: Clp Proteasementioning
confidence: 99%
“…[34][35][36] In contrast to most bacteria, two or more copies of clpP are found in actinobacteria and cyanobacteria and at least one functional copy is essential for viability. 37,38 In Mycobacterium tuberculosis, clpP1 and clpP2 form an operon and both genes are essential. These isoforms work together to create a functional protease by stacking ClpP1 and ClpP2 homoheptamers into a heterotetradecamer.…”
Section: Intracellular Proteolytic Complexesmentioning
confidence: 99%